THE EFFECT OF SPECIAL FOLIAR FERTILISATION APPLIED ON INBRED SUNFLOWER LINES IN HYBRID SUNFLOWER SEED PRODUCTION - Daniela DANA; Irina-Adriana CHIURCIU; Valentina VOICU; Elena SOARE; Ovidiu Mihai POPESCU; Claudia POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents some aspects concerning the influence of special foliar fertilisation on yield and concentration of nutrients in hybrid sunflower seed. This way is useful in seed production, in order to obtain seeds enriched in nutrients, especially in Mo, which caused nutritional disorders in commercial lands. According to the results, the special foliar fertilisers have significantly increased the yields and the Mo concentration in hybrid sunflower seed and have generally positive effect on N, P, K, Zn and Cu concentrations. At the same time, the use of these fertilizers has contributed to Romania's leading position in the production of sunflower seeds, as evidenced by the materials processed on the Eurostat, MADR and NIS websites.